The effect of the geometric structure of the modified slot die on the air field distribution in the meltblowing process. Issue 3 (February 2022) - Wang, Yudong; Qiu, Yiping; Ji, Changchun; Wang, Xinhou; Guan, Fuwang
In order to reduce the fiber diameter and the energy consumption in the meltblowing process, a modified slot die with two blocks was designed in this article. The numerical calculation and the experimental verification of the airflow field under the modified slot die were carried out, and the effect of the block structure parameters on the air field was investigated. The research results indicate that compared to the common slot die, the modified slot die with the blocks could increase the velocity on the spinning line and reduce the rate of the temperature decay on the spinning line. When the block width and the block inclination angle lower, and the block height expands, it could increase the peak of the air velocity, the temperature and the turbulence intensity on the center line of the air field under the modified slot die. The average velocity on the spinning line of the modified die under the conditions of block width = 20 mm, block height = 30 mm and block inclination angle = 60° is the highest.